IMPLEMENTASI FSM (FINITE STATE MACHINE) PADA GAME MUSLIMS EXPLORER’S FAITHFUL MAZE ADVENTURE - Najah Muchsin Sanin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Teknologi Nasional Malang, 2024)
The development of the gaming industry has undergone rapid transformation in the last few decades. In this context, the emphasis in game development is increasingly aimed at deeper and more complex player experiences. In response to these demands, Finite State Machines have become a popular and effective approach in creating organized storylines and better managing characters. By applying FSM to the game